2006
DOI: 10.4321/s0004-06142006000100007
|View full text |Cite
|
Sign up to set email alerts
|

Suprarrenalectomía laparoscópica retroperitoneal como opción minimamente invasiva en el tratamiento de tumores adrenales

Abstract: Retroperitoneoscopic adrenalectomy may be performed effectively and safely, with a low complication rate, independently of the etiology of the lesion. The lateral retroperitoneoscopic access is an excellent option for the minimally invasive treatment of the adrenal glands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Compared with the transperitoneal laparoscopic approach, which is commonly used to resect retroperitoneal tumors[ 13 15 ],the retroperitoneal laparoscopic approach has a few advantages, including shorter operative time, fewer disturbances to abdominal organs, and more rapid convalescence[ 8 , 16 18 ]. A few studies explored the feasibility of retroperitoneal laparoscopic resection of PG (RLPG)[ 11 , 12 , 19 ], and most of them reported successful outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the transperitoneal laparoscopic approach, which is commonly used to resect retroperitoneal tumors[ 13 15 ],the retroperitoneal laparoscopic approach has a few advantages, including shorter operative time, fewer disturbances to abdominal organs, and more rapid convalescence[ 8 , 16 18 ]. A few studies explored the feasibility of retroperitoneal laparoscopic resection of PG (RLPG)[ 11 , 12 , 19 ], and most of them reported successful outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is known that the tumor diameter is an important factor in the surgical management of adrenal tumors using the retroperitoneal laparoscopic technique. Satisfactory clinical results of lateral retroperitoneal laparoscopic adrenalectomy (RLA) for small adrenal tumors have been reported [ 2 4 ]. Scholars have also reported that the largest adrenal benign tumor managed by the transperitoneal approach was 15 cm in diameter, and the largest adrenal benign tumor managed by the retroperitoneal method was 6 cm in diameter.…”
Section: Introductionmentioning
confidence: 99%